2017
DOI: 10.1039/c7ra11056a
|View full text |Cite
|
Sign up to set email alerts
|

Construction of C60-decorated SWCNTs (C60-CNTs)/bismuth-based oxide ternary heterostructures with enhanced photocatalytic activity

Abstract: Ternary heterostructured C60-CNTs/Bi2MoO6 and C60-CNTs/BiVO4 photocatalysts were successfully synthesized. They exhibited enhanced photocatalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The abundance of delocalized electrons in their conjugated p-systems makes carbon materials promising supports, including fullerenes (C 60 ), carbon nanotubes (CNTs), graphitic carbon nitride (g-C 3 N 4 ), and activated carbon bers (ACFs), which can potentially enhance charge separation and transport within the immobilized catalyst. 14,15 Among them all, it was observed that the construction of a semiconductor heterojunction can greatly promote photocatalytic activity. 16,17 Recently, ACFs have attracted much attention as pollutant adsorbents because of their high surface areas, diverse functional groups, narrow pore size distributions, and many raw material precursors.…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of delocalized electrons in their conjugated p-systems makes carbon materials promising supports, including fullerenes (C 60 ), carbon nanotubes (CNTs), graphitic carbon nitride (g-C 3 N 4 ), and activated carbon bers (ACFs), which can potentially enhance charge separation and transport within the immobilized catalyst. 14,15 Among them all, it was observed that the construction of a semiconductor heterojunction can greatly promote photocatalytic activity. 16,17 Recently, ACFs have attracted much attention as pollutant adsorbents because of their high surface areas, diverse functional groups, narrow pore size distributions, and many raw material precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the sample S1 as an example, the high‐resolution of Bi 4 f, Cl 2p and O 1s is respectively analyzed. The two relatively strong peaks at 159.2 and 164.6 eV are assigned to Bi 4f7/2 and Bi 4f5/2 of Bi 3+ , as shown in Figure b. The Cl 2p spectrum in Figure c is resolved into two peaks located at 198 and 199.8 eV, which belong to the binding energies of Cl 2p3/2 and Cl 2p1/2, respectively .…”
Section: Resultsmentioning
confidence: 89%
“…These included: Ag 2 CO 3 /BiVO 4 ; Ag/Ag 2 O–BiVO 4 ; BiVO 4 :Ag; BiVO 4 /BiOCl; BiVO 4 /BiOBr; BiPO 4 /BiVO 4 ; Fe 2 O 3 /3DOM BiVO 4 ; BiVO 4 /InVO 4 ; BiVO 4 /Bi 2 WO 6 ; BiVO 4 /Bi 2 Ti 2 O 7 ; m-BiVO 4 /t-BiVO 4 , and so on [1728]. Also, carbonaceous materials, such as activated carbon (AG), carbon dots, fullerene (C 60 ), carbon nanotubes and graphene have been widely employed for enhancement of photocatalytic activity of BiVO 4 [29]. Graphitic carbon nitride (g-C 3 N 4 ) as a metal-free polymeric semiconductor doped on a Bi-based composite could improve the photocatalytic performance of Bi-based materials [30,31].…”
Section: Introductionmentioning
confidence: 99%